A Pharmacogenetics-Based Approach to Managing Gastroesophageal Reflux Disease: Current Perspectives and Future Steps - Eken E; Estores DS; Cicali EJ; Wiisanen KK; Johnson JA (Dove Medical Press, 2023)
Eda Eken,1,2 David S Estores,3 Emily J Cicali,1,2 Kristin K Wiisanen,1,2 Julie A Johnson1,2 1Department of Pharmacotherapy and Translational Research, College of Pharmacy, University of Florida, Gainesville, FL, USA; 2Center for Pharmacogenomics and Precision Medicine, University of Florida, Gainesville, FL, USA; 3Division of Gastroenterology, Hepatology, and Nutrition, College of Medicine, University of Florida, Gainesville, FL, USACorrespondence: Julie A Johnson, University of Florida, Department of Pharmacotherapy and Translational Research, Box 100486, Gainesville, FL, 32610-0486, USA, Tel +1-352-273-6310, Email Julie.johnson@ufl.eduAbstract: Proton pump inhibitors (PPIs) are commonly used medications to treat acid-related conditions, including gastro-esophageal reflux disease (GERD). Gastroenterology guidelines mention the importance of CYP2C19 in PPI metabolism and the influence of CYP2C19 genetic variations on variable responses to PPIs, but do not currently recommend the genotyping of CYP2C19 prior to prescribing PPIs. There are strong data to support the influence of CYP2C19 genetic variations on the pharmacokinetics of PPIs and clinical outcomes. Existing pharmacogenetic guideline recommendations for dose increases focus on H. pylori and erosive esophagitis indications, but PPIs are also the main therapy for treating GERD. Recent data suggest GERD patients being treated with a PPI may also benefit from genotype-guided dosing. We summarize the literature supporting this contention and highlight future directions for improved management of patients with GERD through precision medicine approaches.Keywords: CYP2C19, precision medicine, proton pump inhibitors, omeprazole, pantoprazole, lansoprazole